(3JfGRY GdbhGfjf Yf GdTQGFY GdbOjeIs - (3GMeO GHQGgje(B, (3MSfs ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 1996)
(3ebOeI(B-(3GdaUd GdChd (B: (3JfGRY GdbhGfjf GdOhdj (B: (3GdeHMK GdChd (B: (3GdYhGed GdJj CYGbJ JWhQ GdbGfhf GdOhdj GdNGU aj GdeLJeYGJ GdbOjeI (B: (3GdeWdH GdChd (B: (3GNJdGa eaghe GdOhdI hGdYdGbGJ GdOhdjI aj GdYGde GdbOje Yf GdYUQ GdMOjK (B: (3GdeWdH GdKGfj (B: (3YOe GdGYJQGa ddCLfHj HGdTNUjI GdbGfhfjI (B: (3GdeHMK GdKGfj (B: (3hSGFd Md eTcdI JfGRY GdbhGfjf aj GdTQGFY GdbOjeI (B: (3GdeWdH GdChd (B: (3OhQ GdCYQGa GdOhdjI aj GdJNaja ef eHOC YOe GdGYJQGa ddCLfHj HGdTNUjI GdbGfhfjI (B: (3GdeWdH GdKGfj (B: (3GdeYGgOGJ GdOhdjI(B-(3GdaUd GdKGfj (B: (3JfGRY GdbhGfjf GdOGNdj (B: (3GdeHMK GdChd (B: (3JfGRY GdbhGfjf aj GdGeHQGWhQjI GdQheGfjI (B: (3GdeWdH GdChd (B: (3JYOO GdbhGfjf aj GdCeHQGWhQjI GdQheGfjI (B: (3GdeWdH GdKGfj (B: (3bGfhf GdTYhH heTcdI JfGRY GdbhGfjf aj GdGeHQGWhQjI GdQheGfjI (B: (3GdeHMK GdKGfj (B: (3JfGRY GdbhGfjf aj eUQ GdHWdejI hGdQheGfjI (B: (3GdeWdH GdChd (B: (3JfGRY GdbhGfjf aj eUQ GdHWdejI (B: (3GdaQY GdChd (B: (3JYOO GdbhGfjf aj eUQ GdHWdejI (B: (3GdeWdH GdKGfj (B: (3JfGRY GdbhGfjf aj eUQ GdQheGfjI(B-(3GdNGJeIs
(3GdeQGLY U(B.221s
Keywords: (3GdbGfhf GdOhdj (B- (3JGQjNs